2023
DOI: 10.1007/s00246-023-03262-2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis Rate of Critical Congenital Heart Disease Remains Inadequate with Significant Racial/Ethnic and Socioeconomic Disparities and Technical Barriers

Arpine Davtyan,
Heidi Ostler,
Ian Fraser Golding
et al.

Abstract: Prenatal diagnosis (preDx) of critical congenital heart disease (CCHD) decreases neonatal morbidity and mortality. Obstetrical fetal cardiac imaging guidelines in 2013 aimed to increase preDx. The objectives of this study were to determine the contemporary preDx rate of CCHD and identify maternal–fetal factors and variations in prenatal care that may be potential barriers. This retrospective single center study evaluated maternal demographics and characteristics of infants with CCHD (requiring cardiac catheter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Studies that included race/ethnicity in their analyses have found consistently lower rates of prenatal detection among Hispanic mothers. In a single-center study of infants with critical CHD, Hispanic infants were significantly less likely to have received a prenatal diagnosis, with 42% lower odds of prenatal detection after accounting for other variables, compared to other racial or ethnic groups [1]. Similarly, a study from the National Birth Defects Prevention Study (NBPDS) found Hispanic mothers were significantly less likely to have a prenatal diagnosis of CHD as compared to non-Hispanic white mothers (9.5% vs. 17.3%, respectively) [7].…”
Section: Race/ethnicitymentioning
confidence: 98%
See 4 more Smart Citations
“…Studies that included race/ethnicity in their analyses have found consistently lower rates of prenatal detection among Hispanic mothers. In a single-center study of infants with critical CHD, Hispanic infants were significantly less likely to have received a prenatal diagnosis, with 42% lower odds of prenatal detection after accounting for other variables, compared to other racial or ethnic groups [1]. Similarly, a study from the National Birth Defects Prevention Study (NBPDS) found Hispanic mothers were significantly less likely to have a prenatal diagnosis of CHD as compared to non-Hispanic white mothers (9.5% vs. 17.3%, respectively) [7].…”
Section: Race/ethnicitymentioning
confidence: 98%
“…A more recent statewide study from Arizona also found private insurance to be significantly associated with higher rates of prenatal detection, as compared to public insurance [14]. Regardless of insurance type, the presence of any health insurance during pregnancy is more likely to increase the likelihood of a prenatal diagnosis of CHD [1]. Even among studies that found no difference in prenatal detection of CHD by insurance type, public insurance was associated with a later gestational age at the time of prenatal diagnosis, as compared to those with private insurance [10,13].…”
Section: Health Insurance Statusmentioning
confidence: 98%
See 3 more Smart Citations